2002
DOI: 10.1016/s0736-0266(01)00109-7
|View full text |Cite
|
Sign up to set email alerts
|

α‐Smooth muscle actin is expressed by fibroblastic cells of the ovine anterior cruciate ligament and its free tendon graft during remodeling

Abstract: Contractile fibroblastic cells expressing the a-smooth muscle actin isoform, so-called myofibroblasts, have been identified to play a possible role during the healing of the medial collateral ligament by means of restoring the tissues in situ strain via extracellular matrix contraction. Recently, these cells have also been identified to be a normal part of the human anterior cruciate ligament. It has been hypothesized that myofibroblasts play a role in the wrinkling of the extracellular matrix. The goal of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
3
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 31 publications
(29 reference statements)
2
56
3
7
Order By: Relevance
“…ACTA2 was also more strongly expressed in the CTGF-stimulated cells. Previous studies have shown that fibroblasts expressing ACTA2 are involved in the earliest stages of fiber bundle formation in the intact as well as the remodelled human ACL [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…ACTA2 was also more strongly expressed in the CTGF-stimulated cells. Previous studies have shown that fibroblasts expressing ACTA2 are involved in the earliest stages of fiber bundle formation in the intact as well as the remodelled human ACL [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Estos fibroblastos contráctiles se expresan progresivamente en la plastia durante los tres primeros meses después de la cirugía [161][209] [246], por lo que se les considera los responsables de restaurar la tensión que se requiere para el proceso de "ligamentización".…”
Section: Fase Inicialunclassified
“…Otros autores relacionan el aumento de vasos [246] y la infiltracion extracelular [228] con la disminución de las propiedades mecánicas de la plastia. Estos hallazgos avalan otros muchos trabajos que encuentran que las propiedades mecánicas son mínimas en la fase de proliferación del injerto, aproximadamente entre la 6ª y 8ª Es un proceso de debilitamiento de la plastia hasta la 6ª semana que por otra parte mejora la integración del injerto en la plastia.…”
Section: Fase Inicialunclassified
See 1 more Smart Citation
“…Myofibroblasts, identified as α-smooth muscle actin (α-SMA)-positive fibroblasts [15,16], have been observed in normal and healing tendons [17,18] [19] and in the intact and injured human ACL [20][21][22]. They contribute substantially to the contractile phase of MCL healing, allowing recovery of its original length [23].…”
Section: Introductionmentioning
confidence: 99%